Hungary : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper reviews the relationship between real GDP growth and domestic bank lending to the private sector in Hungary after the global financial crisis, It draws on a cross-country analysis of European countries. The recessions that followed the crisis were deeper and lasted longer than the average recession. Hungary, like some other countries, experienced a creditless recovery. Although it is difficult to disentangle the causes, this analysis concludes that (1) both credit demand and supply were hurt by the crisis; (2) key factors influencing credit developments include loan quality, deposit funding, and bank capital, as well as the macroeconomic environment; and (3) lending by Hungarian banks to the private sector finally seems to be picking up.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet